Digital Popularity and Self-Confidence: Examining the Role of Instagram Followers among University Students - Ersya Shafira Chairani; Hari Otang Sasmita; Guruh Ramdani; Fahmi Fuad Cholagi (Poltekkes Kemenkes Jakarta III, 2026)
Abstract The rapid expansion of social media has transformed how university students construct identity and evaluate self-worth, with Instagram emerging as a prominent platform for social validation. This study aimed to examine the relationship between Instagram follower count and self-confidence among university students, positioning follower count as a psychosocial indicator of digital social approval. Using a quantitative cross-sectional design, data were collected through an online survey administered to 76 undergraduate students who actively used Instagram. Self-confidence was measured using a Likert-scale questionnaire adapted from social self-efficacy theory, while follower count was assessed through self-reported data. Instrument validity and reliability were confirmed prior to analysis.Normality testing indicated non-normality, leading to the use of Spearman’s rank-order correlation to examine the association between variables. The results revealed a strong, statistically significant positive relationship between Instagram follower count and self-confidence, indicating that students with higher follower counts reported greater confidence in social interactions. These findings suggest that follower count serves as a meaningful form of social validation, influencing students’ self-perceptions in both digital and offline contexts.The study highlights the psychological implications of digital popularity metrics and underscores the need for higher education institutions to promote digital literacy and mental health awareness. By fostering critical engagement with social media, universities can help students develop healthier relationships with online validation and support more resilient forms of self-confidence.